Alternatives in art education - Memorial University of Newfoundland. Extension Service (Producer) (Memorial University of Newfoundland Extension Service, 1974)
Developed for the use of teachers in Newfoundland and Labrador, explores and compares alternative approaches to the teaching of art. Extension Service programs are child-based, placing an emphasis on child development rather than on the product or the acquiring of skills. Condition: Opening frames are missing. Tape transferred from defective master. Tracking is very poor in places including credits at the end